Designing an Optimal Control LQT for Controlling and Guidance of Missile - Rusdhianto Effendie AK; Muhamad Rafif Prasetyo; Zulkifli Hidayat (Department of Electrical Engineering ITS and FORTEI, 2018)
Missile has to be controlled and follow the commanded guidance in order to make its flight hit the target. Since missile has a nonlinear characteristic and coupled dynamic equation, controlling a missile has become more complex. Linear Quadratic Tracking (LQT) is one of optimal control theory where its objective is to make the output of a system tracks its reference as close as possible while minimize or maximize a desired performance index. In this paper, an autopilot for missile is designed which consists nonlinear state feedback decoupler and LQT controller. Pursuit Guidance is used for the guidance law. A missile-target engagement simulation is created using 2 kinds of target; static target and dynamic target. By using static target, the mean of the closest distance between missile and the target is 0.45 meters and by using dynamic target the mean of the closest distance between missile and the target is 2.562 meters. Keywords: guided missile, Linear Quadratic Tracking, Nonlinear State Feedback Decoupler, Pursuit Guidance